Persistence of the Immune Response to an Intramuscular Bivalent (GI.1/GII.4) Norovirus Vaccine in Adults - Geert Leroux-Roels; Robert L. Atmar; Jakob P. Cramer; Ian Escudero; Astrid Borkowski (Vaccines)
Background: Major global economic and health burdens due to norovirus gastroenteritis could be addressed by an effective vaccine. Methods: In this study, 428 adult recipients of various compositions of the norovirus vaccine candidate, HIL-214, were followed for 5 years, to assess immune responses to its virus-like particle antigens, GI.1 and GII.4c. Serum antibodies and peripheral-blood antibody-secreting cells (ASCs) were measured. This report focuses on the single-dose 15/50 (µg GI.1/GII.4c) composition, which had been selected for further clinical development. Results: For single-dose 15/50 recipients (N = 105), GI.1-specific and GII.4c-specific histoblood-group antigen-blocking (HBGA) antibodies appeared to have persisted to 5 years, waning from a peak at 4 to 8 weeks, and plateauing above baseline after 3 years. From 3 to 5 years, GI.1-specific GMTs ranged between 53 (95%CI, 40–71) and 60 (95%CI, 46–77; N = 69–97) and were approximately 2-fold above the baseline GMT (24 (95%CI, 20–28); N = 105). GII.4c-specific GMTs ranged between 103 (95%CI, 77–138) and 114 (95%CI, 86–152; N = 70–97) and were above baseline, but by less than 2-fold (70 (95%CI, 53–92); N = 105). Similar kinetics were observed for pan-Ig titers and ASCs in a subset. Similar kinetics were also observed for HBGA and pan-Ig titers in recipients of other 15/50 dosages. Conclusions: Immune responses to HIL-214 in adults appear to persist for five years.